The independent association of plateletcrit with long-term outcomes in patients undergoing primary percutaneous coronary intervention - (:unkn) unknown (W B SAUNDERS CO-ELSEVIER INC, 2014)
Purpose: Platelets play a key role in the genesis of thrombosis. Plateletcrit (PCT) provides complete information on total platelet mass. The relationship between PCT values and long-term outcomes in patients with ST-segment elevation myocardial infarction (STEMI) who undergo primary angioplasty is not known. We sought to determine the effect of PCT values on the outcomes of primary angioplasty for STEMI. Methods: Overall, 2572 consecutive STEMI patients (mean age, 56.6 +/- 11.8 years) undergoing primary percutaneous coronary intervention were enrolled retrospectively into the present study. Plateletcrit at admission was measured as part of the automated complete blood count. Patients were classified into 2 groups: high PCT (>0.237, n = 852) and nonhigh PCT (<0.237, n = 1720). Clinical characteristics and in-hospital and long-term (median, 21 months) outcomes of primary angioplasty were analyzed. Results: A higher in-hospital shock rate was observed among patients with high PCT values compared with those with nonhigh PCT values (6.5 vs 3.8%, respectively; P = .003). The long-term cardiovascular prognosis was worse for patients with high PCT values (Kaplan-Meier, log-rank test; P = .007). We used Cox proportional hazard models to examine the association between PCT and adverse clinical outcomes. High PCT values were also an independent predictor of cardiovascular mortality (hazard ratio, 1.85; 95% confidence interval, 1.061-3.22; P = .03). Conclusion: High PCT values on admission are independently associated with long-term adverse outcomes in patients with STEMI who undergo primary angioplasty. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: ST-segment elevation myocardial infarction; Plateletcrit; Angioplasty; PRIMARY ANGIOPLASTY; VOLUME; PREDICTORS; ACTIVATION; ADMISSION; INDEXES; COUNT; FLOW